A Comparison of Lithuanian and Swedish Old Age Pension Systems - Medaiskis, Teodoras; Eirošius, Šarūnas (Ekonomika, 2019)
[full article and abstract in English]The aim of this study is to compare Lithuanian and Swedish pension systems from the point of view of their design and performance in order to elaborate reasonable recommendations to Lithuanian pension policy based on the best Swedish experience. Swedish income, premium and guaranteed old-age pensions system are compared with the analogous Lithuanian system of the “first,” “second” pillars and the “social” pensions. The main features of the systems are discussed, and the performance of the systems, mainly from the point of view of adequacy, is compared. The differences in system design and performance are identified, and the possible reasons of these differences are examined. Special attention is paid to differences in financing and the approach to the definition of benefits. The Lithuanian pension points approach is compared to the Swedish Notional Defined Contribution (NDC) approach. Each system is analyzed, and the relevance of transforming the Lithuanian first pillar pensions into a NDC system is examined.
Keywords: Pensions; NDC system; pension reforms; pension adequacy and sustainability